1998
DOI: 10.1063/1.121118
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth of highly oriented Pb(Zr0.5Ti0.5)O3 thin films by low-temperature metal–organic chemical vapor deposition

Abstract: Highly oriented, polycrystalline Pb(Zr0.5Ti0.5)O3 (PZT) thin films were successfully grown on RuO2/SiO2/(001)Si using metal–organic chemical vapor deposition (MOCVD) at 525 °C. The orientation of the PZT film was controlled by using MOCVD-deposited highly textured RuO2 bottom electrodes. A (001)-oriented PZT film was observed for growth on (101)-textured RuO2. In contrast, for (110) RuO2, the growth of (001) PZT was greatly suppressed while the growth of both (110) and (111) were enhanced, resulting in a poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…These physical vapor deposition techniques yielded high‐quality oxide superconductor films just a few nanometers in thickness, 115–117 superlattices of superconducting oxides with atomic‐scale thickness control and abrupt interfaces, 110,118–126 and the construction of new oxide superconducting phases with atomic layer precision 76,127 . Chemical techniques including metal‐organic chemical vapor deposition (MOCVD) 128–143 and chemical solution deposition (CSD) 144–148 have also been adapted and applied to functional oxides, particularly ferroelectrics. In recent years, a growing cadre of researchers has applied these physical and chemical techniques with increasing precision to the growth of an ever‐broadening set of functional oxide materials.…”
Section: Synthesis Of Epitaxial Oxide Films By Pulsed‐laser Deposmentioning
confidence: 99%
“…These physical vapor deposition techniques yielded high‐quality oxide superconductor films just a few nanometers in thickness, 115–117 superlattices of superconducting oxides with atomic‐scale thickness control and abrupt interfaces, 110,118–126 and the construction of new oxide superconducting phases with atomic layer precision 76,127 . Chemical techniques including metal‐organic chemical vapor deposition (MOCVD) 128–143 and chemical solution deposition (CSD) 144–148 have also been adapted and applied to functional oxides, particularly ferroelectrics. In recent years, a growing cadre of researchers has applied these physical and chemical techniques with increasing precision to the growth of an ever‐broadening set of functional oxide materials.…”
Section: Synthesis Of Epitaxial Oxide Films By Pulsed‐laser Deposmentioning
confidence: 99%
“…Several thin film growth techniques such as molecular beam epitaxy, [80][81][82][83] pulsed laser deposition, [84][85][86] sputtering, [87][88][89][90][91][92][93] metal-organic chemical vapor deposition, [94][95][96][97][98] and chemical solution deposition 99 etc. have been used to synthesize high quality complex oxide thin films.…”
Section: Synthesis and Characterization Of Thermoelectric Complementioning
confidence: 99%
“…Small grains and dark phases were found in the surface of (c) PZT/RuO 2 thin films. It was reported that these dark phases were associated with Pbdeficient phyrochlore-like phases [12]. Fig.…”
Section: Resultsmentioning
confidence: 98%